Contract enforcement and institutions among the Maghribi traders: refuting Edwards and Ogilvie - Avner Greif (Center for Economic Studies and ifo Institute (CESifo), 2008)
Edwards and Ogilvie (2008) dispute the empirical basis for the view (Greif, e.g., 1989, 1994, 2006) that multilateral reputation mechanism mitigated agency problems among the eleventh-century Maghribi traders. They assert that the relations among merchants and agents were law-based. This paper refutes this assertion using quantitative and documentary evidence thereby vindicating the position that the legal system had a marginal role in mitigating agency problems in long-distance trade in this historical era.** Edwards and Ogilvie constantly present legal actions in non-trade related legal cases as evidence for a reliance on the legal system for matters pertaining to long-distance trade. Their criticism of Greif's documentary analysis also fails scrutiny. The claim that merchants' relations with their overseas agents were law-based is wrong. This paper is based on quantitative analyses of the corpuses containing the hundreds of documents on which the literature relies and a careful review of the documents and the literature Edwards and Ogilvie cite. Their assertion is shown to be based on unrepresentative and irrelevant examples, an inaccurate description of the literature, and a consistent misreading of the few sources they consulted. In particular, their examples for the use of the court are mainly taken from mandatory legal procedures associated with sorting out the assets and liabilities of deceased traders' estates. Such examples do not support the claim that agency relations were law-based. The quantitative analysis reveals that empirical basis for the multilateral reputation view is stronger than originally perceived. This paper also sheds light on the roles of the legal system and reputation mechanism during this period.
Keywords: O17; 330; Vertrag; Normbefolgung; Prestige; Soziales Netzwerk; Außenhandelsgeschichte; Mittelalter; Mittelmeerraum